1981
DOI: 10.1002/jlac.198119810311
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrische Synthesen über heterocyclische Zwischenstufen, IV Asymmetrische Synthese von α‐Methylphenylalanin und seinen Analoga durch Alkylieren von 1‐chiral substituiertem 4‐Methyl‐2‐imidazolin‐5‐on

Abstract: Herrn Prof. S. Hiinig zum 60. Geburtstag gewidmet. La13t man 2-Isocyan-N-[(S)-l'-phenylethyl]propionsaureamid (3 a) mitButyllithium oder Kaliumtert-butanolat ( -70 "C, Tetrahydrofuran) reagieren, tritt erst Metallierung und dann (bei ca. -20 "C) Cyclisierung zum anionisierten 4-Methyl-l-[(S)-l'-phenylethyl]-2-imidazolin-5-on (8) ein. Dieses reagiert mit Benzylhalogeniden oder Heterobenzylhalogeniden mit weit uber 95proz. asymmetrischer Induktion (d. e. = diastereomeric excess) zu den (4S)-CBenzyl-oder (4S)-4-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The chiral amine auxiliary can be recovered. 522 Although the chemistry relevant to this section has been described in detail in the corresponding sections above, we wish to discuss some additional syntheses of natural and unnatural amino acids to further demonstrate the synthetic utility of isocyanoacetates. Thus, (-)-(2R,3S)-3-hydroxylysine 1178, a naturally occurring amino acid, was synthesized using a gold-catalyzed asymmetric aldol reaction.…”
Section: Synthesis Of Amino Acid Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…The chiral amine auxiliary can be recovered. 522 Although the chemistry relevant to this section has been described in detail in the corresponding sections above, we wish to discuss some additional syntheses of natural and unnatural amino acids to further demonstrate the synthetic utility of isocyanoacetates. Thus, (-)-(2R,3S)-3-hydroxylysine 1178, a naturally occurring amino acid, was synthesized using a gold-catalyzed asymmetric aldol reaction.…”
Section: Synthesis Of Amino Acid Derivativesmentioning
confidence: 99%
“…He found that alkylation of N-[(S)-phenetyl]-2-isocyanopropionamides 1192 by benzyl halides proceeds with high diastereoselectivity, whereas with nonbenzylic alkyl halides, the de is much lower. 522 Furthermore, Scho ¨llkopf has described the cyclopropanation of formylaminoacrylates 1195a and isocyanoacrylates 1195b by dimethylsulfoxonium methylide, 529 a method used for the preparation of aminocyclopropane carboxylic acid (ACC) derivatives 1196 (Scheme 297). 530,531…”
Section: Synthesis Of Amino Acid Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Including the current approach, now four complementary synthetic pathways are available to access this important starting material class. ,, Current evaluation of this isocyanide class for use in new IMCR is ongoing in our laboratory. We are also investigating the broad use of the described compound class in the synthesis of 1-alkyl-4-carboxamidoimidazoles, 2,3,4-trisubstituted pyrroles, isoxazolinopyrroles, macrocycles, lennoxamine-type natural products, silver catalyzed imidazolidines and oxazoles, oxazolines, spiroimidazolones, 10b, peptides, 1 H -imidazole-2-thiones, 2,4-bis(arylthio)-5-[ N -alkyl- N -phenylamino]oxazoles,9b α-keto esters, mesoionic 3-alkyl-2-(arylthio)-1,3-diazolium-4-olates, 2-aminoimidazoles, optically active threo-β-hydroxyamino acids, 2-imidazolin-5-ones, 5-amino oxazoles,9a or 1-oxo-1,2-dihydroisoquinoline-3-carboxylic acid derivatives . This class of isocyanides will provide the foundation of focused and general libraries for use in the discovery of biologically active compounds.…”
Section: Introductionmentioning
confidence: 99%
“…), the enolate geometry may be Z, in accordance with the literature precedence and favored by the coordination C-O-Li-OLP. 10 The orientation of the C-H bond of the chiral auxiliary towards the oxygen atom and the relative size of phenyl and methyl groups determines the preferred direction of benzyl bromide addition, 11 in this case for the re face, which leads to (R,S)-4 diastereomer as principal product. Additionally, the reaction appears to be operating under kinetic control, since no evidence of reversibility was observed and the diastereoselectivity was independent of reaction time (Table 1, entry 5).…”
mentioning
confidence: 99%